Subjective Norms Predict Intention to Covid-19 Vaccination among Older Adults in Southern Iran: a Community-based Cross-sectional Study - Mahsa Yarelahi; Elham Rezaian; Farzaneh Bahadori; Zeinab Sahraian; Somayeh Abolghsemi; Masoud Karimi (Shiraz University of Medical Sciences, 2023)
Background: The success of the vaccination programs against covid-19 depends on the level of community vaccine acceptance. The present study aimed to investigate the predictors of older adults' intention to uptake the covid-19 vaccine in older adults.Methods: This cross-sectional study was conducted on 345 older adults in Jahrom, southern Iran. Participants were enrolled by stratified random sampling. The data collection tool was a researcher-made questionnaire consisting of items based on the health belief model (HBM), Theory of planned behavior (TPB) constructs and demographic information. Descriptive statistics, Spearman's correlation, and Ordinal logistic regression analysis were used for data analysis using SPSS version 25. The level of significance was set at 0. 05.Results: The mean age of participants was 67.7 (7.2) years. Most of the participants (51.3%) intended to receive the vaccine. Perceived barriers (r=-0.201), perceived benefits (r=0.302), selfefficacy (r=0.269), and subjective norms (r=0.387) had significant associations with the intention to vaccine (P<0.001). Subjective norms (β=0.159, P<0.001) were the most powerful predictor of intention to vaccine, followed by perceived benefits (β=0.112, P=0.035) and self-efficacy (β=0.086, P=0.038).Conclusion: health professionals should promote positive attitudes toward the covid-19 vaccine and reports about vaccination by celebrities and trusted people to persuade older adults to receive the covid-19 vaccine.